Respons Pertumbuhan Dan Produksi Sawi (Brassica Juncea) Terhadap Berbagai Jenis Nutrisi Dan Media Tanam Dalam Sistem Hidroponik Irigasi Tetes: The Response of Growth and Production of Mustard (Brassica Juncea) to Various Nutrients and Media for Hydroponic Planting in Drip Irrigation System - Saleh, Zasmitha; Rampisela, Agnes Dorothea; Jayadi, Muh (Universitas Hasanuddin, 2025)
The carrying capacity of agricultural land is important to determine the extent of the ability of the land to support food needs, but wherever there is a land problem that results in low productivity of agricultural products. Organic farming is very important. The use of organic matter for soil fertility is expected that farmers will be more aware of using liquid organic fertilizers (POC) and the use of plant waste as a planting medium. The hydroponic system replaces the function of the soil as a support for plant roots by circulating nutrients, water and oxygen into the garden media. Provision of water in small and sustainable volumes through drip irrigation aims to keep the planting medium moist and avoid losses such as percolation and runoff. Automatic water control in drip irrigation is a new breakthrough to increase the efficiency of water use in the root zone. Hydroponics as an innovation meets food needs independently as a solution to the limited carrying capacity of agricultural land by knowing the different effects of nutrition and planting media on the response to growth and mustard production. This research was conducted in Tamalanrea District with climatic conditions according to the Makassar City Central Statistics Agency in 2020 with an average; daily temperature 28.39 oC, humidity 81%, rainfall 229.16 mm3, daily amount of rain 15 days / month and length of exposure 73.25%, Makassar City. Research on the growth response of mustard plants to determine the effect of the use of nutrients and media on mustard greens. The study used a factorial nested design consisting of two factors. The first factor is the nutritional treatment (N), namely Nb = POC for fruit, Ns = POC for vegetables and Nx = nutrition AB Mix. The second factor is the treatment of the planting medium (M), namely Mrw = rockwool, Mas = husk charcoal and Mcp = cocopeat. The nutritional composition of the fruit liquid organic fertilizer (Nb) in the treatment gave the best results with an average of 407.27 cm2 of leaves, 26.18 g of fresh weight of leaves and stems, 10.82 g of fresh root weight, 2.29 mL of root volume, dry weight of leaves and stem 0.26 g, and root dry weight 0.14 g. whereas in the planting medium rangsekam (Mas) gave the highest response to growth and production of mustard greens on the observed parameters with an average plant height of 11.53 cm, number of leaves 6.83, leaf area 393.86 cm2, chlorophyll index 248525.91 , leaf and stem fresh weight 27.49 g, root fresh weight 8.56 cm, root volume 2.30 mL, plant ratio 3.50%, and root dry weight 0.13. Nutritional treatment of fruit POC (Nb) and rangsekam plant media gave the best results in mustard greens.